Picornavirus IRESes and the poly(A) tail jointly promote cap-independent translation in a mammalian cell-free system. - Bergamini, G (2000)
In eukaryotic cells, efficient translation of most cellular mRNAs requires the synergistic interplay between the m7GpppN cap structure and the poly(A) tail during initiation. We have developed and characterized a cell-free system from human HeLa cells that recapitulates this important feature, displaying more than one order of magnitude of translational synergism between the cap structure and the poly(A) tail. The stimulation of cap-dependent translation by the poly(A) tail is length-dependent, but not mediated by changes in mRNA stability. Using this system, we investigated the effect of the poly(A) tail on the translation of picornaviral RNAs, which are naturally polyadenylated but initiate translation via internal ribosome entry sites (IRESs). We show that translation driven by the IRESs of poliovirus (PV), encephalomyocarditis virus (EMCV), and hepatitis A virus is also significantly augmented by a poly(A) tail, ranging from an approximately 3-fold stimulation for the EMCV-IRES to a more than 10-fold effect for the PV IRES. These results raise interesting questions concerning the underlying molecular mechanism(s). The cell-free system described here should prove useful in studying these questions as well as providing a general biochemical tool to examine the translation initiation pathway in a more physiological setting.